Connecting theory and practice in digital humanities information work. (25th March 2017) - Clement, Tanya E.; Carter, Daniel
Abstract : The omnipresence and escalating efficiency of digital, networked information systems alongside the resulting deluge of digital corpora, apps, software, and data has coincided with increased concerns in the humanities with new topics and methods of inquiry. In particular, digital humanities (DH), the subfield that has emerged as the site of most of this work, has received growing attention in higher education in recent years. This study seeks to facilitate a better understanding of digital humanities by studying the motivations and practices of digital humanists as information workers in the humanities. To this end, we observe information work through interviews with DH scholars about their work practices and through a survey of DH programs such as graduate degrees, certificates, minors, and training institutes. In this study we focus on how the goals behind methodology (a link between theories and method) surface in everyday DH work practices and in DH curricula in order to investigate if the critiques that have appeared in relation to DH information work are well founded and to suggest alternative narratives about information work in DH that will help advance the impact of the field in the humanities and beyond.